2015
DOI: 10.1002/bmc.3587
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic profile and antioxidant effects of various parts of Artemisia annua L.

Abstract: An annual Korean weed, Artemisia annua L., has been used as a folk medicine for the treatment of a number of diseases. Remarkably, among the 32 polyphenols characterized in various parts of plant tissue, including flowers, leafs, stems and roots, 10 compounds were detected for the first time using liquid chromatography-tandem mass spectrometry (LC/MS/MS). The quantification method was validated using structurally related external standards with determination coefficients (R(2) ) ≥0.9995. The limits of detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Polyphenols were extracted from Korean A. annua L. (pKAL) and characterized by Professor Shin (Gyeongsang National University, Jinju, Korea) [5]. Briefly, the lyophilized Korean A. annua L. (KAL) tissues including roots, stems, leaves, and flowers (10 g) were ground into powder, extracted in ethyl acetate (300 mL) at 80 • C for 20 h, and eluted with a mixture of methanol:dichloromethane (1:5, 25 mL).…”
Section: Preparation Of Polyphenols From Korean Artemisia Annua Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenols were extracted from Korean A. annua L. (pKAL) and characterized by Professor Shin (Gyeongsang National University, Jinju, Korea) [5]. Briefly, the lyophilized Korean A. annua L. (KAL) tissues including roots, stems, leaves, and flowers (10 g) were ground into powder, extracted in ethyl acetate (300 mL) at 80 • C for 20 h, and eluted with a mixture of methanol:dichloromethane (1:5, 25 mL).…”
Section: Preparation Of Polyphenols From Korean Artemisia Annua Lmentioning
confidence: 99%
“…Among phytochemicals, natural polyphenols are abundantly present in various edible fruits, vegetables and herbs, which are assumed to be related to a reduction in cancer risk [2,3]. Artemisia annua L., (Gaddongsook, Korean), an annual herb, has been used for a long time as a Korean folk medicine for the treatment of malaria, fever, and neurologic disorders [4,5]. In addition, it possesses anti-cancer activity [6].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15] Reported vital pharmacological activities effectuated by flavonoids in A. annua include antioxidant, inhibition of immune mediators of angiogenesis, prophylactic effects in malaria and related fevers, and antimalaria parasite. 8,[16][17][18][19][20] Luteolin and apigenin are flavonoids that are commonly found in different plant species that are associated with a broad spectrum of pharmacological activities, including antimalarial, anti-inflammatory, antioxidant, and anticancer. [20][21][22][23] However, the efficacy of drugs that contain flavonoids can vary according to environmental conditions and season of harvest or growth stage.…”
Section: Introductionmentioning
confidence: 99%
“…The polyphenols in the SM plant were characterized in our recent study, and about 14 polyphenol compounds have been reported: five hydroxycinnamates (two caffeoylquinic acid isomers, dicaffeoylquinic acid, 3,4,5-Otricaffeoylquinic acid, calcelarioside A), eight flavonoids (6,8-di-C-glucosylapigenin, 6-Carabinosyl-8-C-glucosylapigenin, two amentoflavone isomer, kaempferol-3-O-rutinoside, kaempferol-3-O-glucuronide, quercetin-dimethyl -ether, skullcapflavon Ⅱ), and one lignan (secoisolariciresinol) (Kim 2016). Polyphenols play an effective role as antioxidants that can scavenge reactive oxygen species (ROSs), thereby retarding the pathogenesis of age-related degenerative diseases, such as diabetes, cardiovascular disease, and cancer (Kim et al 2016;Kim 2014;Song et al 2016). Plant polyphenols not only determine the functional quality in terms of plant products but also serve as an important factor in their potential application in the fields of nutrition and pharmacology (Carvalho et al 2011) and in the food industry to increase selflife (Wei et al 2017), on which scientists have been concentrating with great interest.…”
Section: Introductionmentioning
confidence: 99%